Front Cover Picture: Traceless Directing Group Assisted Cobalt‐Catalyzed C−H Carbonylation of Benzylamines (Adv. Synth. Catal. 21/2017). Issue 21 (16th October 2017) - Ling, Fei; Ai, Chongren; Lv, Yaping; Zhong, Weihui
Abstract : The front cover picture, provided by Weihui Zhong and co‐workers, illustrates the first example of cobalt‐catalyzed C( sp 2 )−H carbonylation of benzylamines using a traceless directing group, which was successfully applied to the synthesis of N ‐unprotected isoindolinones through direct C−H/N−H bonds activation. This protocol tolerates a variety of functional groups and provides a facile and efficient method for the formal synthesis of (+)‐garenoxacin. Details of this work can be found in the communication on pages 3707–3712 (F. Ling, C. Ai, Y. Lv, W. Zhong, Adv. Synth. Catal .2017, 359, 3707–3712; DOI:10.1002/adsc.201700780 )